Comments on systematics and distribution of Thylodrias contractus (Coleoptera Dermestoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Thylodrias contractus Motsch. found in food-stuffs and in private houses of Milan, is taken into consideration from biologie, morphologic and systematic points of view with particular regard to its position in the superfamily Dermestoidea. Adults and larvae have been examined and morphologic details (bristles, antennae, wings and mouthparts) are figured. Data on reproduction, growth and dietary are given too.